Use of EQUORAL(R) in de novo renal transplant recipients - Zadrazil, Josef; Al Jabry, Sadek; Bachleda, Petr; Gibejova, Agata (Biomedical papers, 2004)
This paper presents our experience to date with using a cyclosporine formulation Equoral(R) (IVAX Pharmaceuticals) together with mycophenolate mofetil plus a steroid immunosuppressive regimen in the treatment of de novo renal transplant recipients. Ten cadaveric donor renal transplant recipients of mean age 51.6 years (range 37-66) were followed up over 6 months for the development of rejection attacks and side effects. All patients received prednisolone, mycophenolate mofetil (1 g/day during the first 5 days posttransplant and then 20 mg/kg/day) plus cyclosporine (3 mg/kg/day). Biopsy proven acute rejection episodes were observed in 2 out of 10 patients (20 %). Six months patient as well as renal graft survival rate was 100 %. The development of graft function was immediate after transplantation. The mean serum creatinine levels were gradually decreased. Over the 6-month posttransplant period, the function of the graft was satisfactory and stable. The majority of observed adverse events were those commonly reported with the use of cyclosporine and they resolved with a reduction in cyclosporine dose. Equoral(R) treatment demonstrated an acceptable safety profile with maintenance of adequate renal function without incidence of malignancy/lymphoproliferative disease or serious infections. In conclusion, Equoral(R) plus mycophenolate mofetil immunosuppression seems effective and safe on terms acute rejection rates, patient and renal graft survival rates and side profiles.
Keywords: Cyclosporine A/Renal transplantation de novo/Equoral(R)